Financial Instability in the Earned Income Tax Credit Program: Can Advanced Periodic Payments Ameliorate Systemic Stressors?. Issue 6 (November 2021) - Greenlee, Andrew; Kramer, Karen; Andrade, Flavia; Bellisle, Dylan; Blanks, Renee; Mendenhall, Ruby
The Earned Income Tax Credit (EITC) serves more than 26 million U.S. tax filers every year. The EITC is distributed annually at tax time; however, past research suggests that lump-sum disbursements leave households with a lack of funds to deal with financial emergencies throughout the year. Drawing upon the data from a pilot program conducted in 2014–2015 in Chicago, this study analyzes how advanced periodic payments help mitigate financial instability for EITC recipients. Interview participants relate that advanced periodic payments result in a reduction in perceived stress, lower levels of debt, fewer unpaid bills, and the ability to engage youth in extracurricular activities. The findings provide a unique perspective on the ways in which low-income households cope with financial instability and stress and suggest that payment frequency options can play a small but important role in the way in which the EITC operates as a support mechanism.